Effects of protein and amino-acid supplementation on athletic performance - Kreider, R. B. (1999)
This review evaluates the theoretical rationale and potential effects on athletic performance of protein, purported anabolic amino acids,branched-chain amino acids, glutamine, creatine, and hydroxymethylbutyrate (HMB). Of the nutrients reviewed, creatine appears to have the greatest ergogenic potential for athletes involved in intense training.